Treatment of osteoarthritic knee with high tibial osteotomy and allogeneic human umbilical cord blood–derived mesenchymal stem cells combined with hyaluronate hydrogel composite - Bo Seung Bae; Jae Woong Jung; Gyeong Ok Jo; Seon Ae Kim; Eun Jeong Go; Mi-La Cho; Asode Ananthram Shetty; Seok Jung Kim (Stem Cell Research & Therapy)
Abstract Background Delaying total knee arthroplasty is crucial for middle-aged patients with severe osteoarthritis. The long-term outcomes of high tibial osteotomy (HTO) remain uncertain. Recently, mesenchymal stem cells (MSCs) have shown promising potential in enhancing cartilage regeneration. Therefore, this study aimed to assess cartilage regeneration following the implantation of allogeneic human umbilical cord blood–derived mesenchymal stem cells (hUCB-MSCs) with HTO. Methods In this case series, ten patients underwent hUCB-MSC implantation with HTO. The median age was 58.50 (range: 57.00–60.00) years, and the mean body mass index was 27.81 (range: 24.42–32.24) kg/m2. Clinical outcomes, including the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), visual analog scale (VAS), Physical Component Score (PCS) and Mental Component Score (MCS) from the 36-Item Short-Form Health Survey (SF-36), were evaluated 6 months, 1 year, and 2 years postoperatively. Cartilage status of the medial femoral condyle (MFC) was assessed during hardware removal surgery, at least 2 years after the initial procedure, and compared with preoperative MFC cartilage status regarding lesion size and International Cartilage Repair Society (ICRS) grade. Radiological assessments included the Kellgren–Lawrence (KL) grading system for medial compartment osteoarthritis and hip–knee–ankle (HKA) angle. Results Significant improvements were observed in WOMAC scores (preoperative: 57.00 (range: 44.75–63.00), postoperative: 27.50 (range: 22.25–28.75)), VAS scores (preoperative: 66.25 (range: 48.00–74.25), postoperative: 26.25 (range: 14.50–31.13)), SF-36 PCS (preoperative: 27.97 (range: 26.64–31.25), postoperative: 55.31 (range: 51.64–62.50)), and SF-36 MCS (preoperative: 41.04 (range: 29.95–50.96), postoperative: 63.18 (range: 53.83–65.16)) 2 years postoperatively (p = 0.002, 0.002, 0.002, and 0.020, respectively). The MFC chondral lesion demonstrated significant improvement in both lesion size (preoperative: 7.00 cm² (range: 4.38–10.50 cm²), postoperative: 0.16 cm² (range: 0.00–1.75 cm²), p = 0.002) and ICRS grade (preoperative: 4 (range: 4–4), postoperative: 1 (range: 1–2.25), p = 0.002). Additionally, the KL grade significantly decreased from 3 (range: 3–3) preoperatively to 2 (range: 2–2) postoperatively, while the HKA angle was corrected from 7.50° (range: 7.00–10.25°) preoperatively to -1.00° (range: -3.5–0.00°) postoperatively. Conclusions hUCB-MSC implantation with HTO is an effective treatment for medial compartment osteoarthritis and varus deformities, resulting in significant improvements in cartilage regeneration and overall clinical outcomes. Trial registration NCT04234412.